CUBISM “TWO FACE OF THE GIRLS” - Melda Eksiyana; Ruth Ambarsari; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2021)
The fashion design in this Final Project aims to create a special party fashion design that combines the source of ideas and selected fashion styles. The source of the idea for this design is Cubism